Am I Really Bipolar? Personal Accounts of the Experience of Being Diagnosed With Bipolar II Disorder - Johansson, Cecilia; Werbart, Andrzej (Frontiers in Psychology, 2020)
Bipolar disorder (BD) is a complex and chronic mental illness with highs and lows beyond the ordinary, which induces a significant risk of suicide. The aim of this study was to explore the experience of being diagnosed with BD and the impact that receiving a correct diagnosis had had on life situations and relationships with others. Semi-structured qualitative interviews were conducted with seven people diagnosed with BD. The results showed that the primary treatment all participants had received or were currently receiving was pharmacotherapy, typically without any psychological component. A major concern that arose was delayed diagnosis, leading to inadequate treatment, and lack of knowledge among professionals about non-typical forms of BD. Moreover, the experiences of others’ reactions were multifold, though generally surprisingly positive. Generally, the participants had learned to recognize, understand and tackle early symptoms of both hypomanic and depressive episodes to avoid developing a full-blown acute episode. This study highlights the crucial importance of a collaborative relationship between the clinician and the patient.